Efektivitas Mozaik Bahan Alam (Sisik Ikan) terhadap Motorik Halus Anak - Rici Rulmalia; Zulminiati Zulminiati (Universitas Trunojoyo Madura, 2019)
This research to knowing the effectiveness of natural mosaic materials (fish scales) on children's fine motor skills In Kindergarten Jabal Rahmah Padang. This type of research is quantitative method with the type of experiments or research quashi experimental by using natural mosaic (fish scales) the results of this study obtained an average value obtained from the experimental class which uses higher natural ingredients (fish scales) (82.50) compared to the control class that uses seashell mosaic (73,12). Based on the calculation the t-test was obtained that tcount is greater than t table shows that there is a significant effect on fine motor.